TRANSDERMAL SOLID LIPID NANOPARTICLES OF CLOMIPHENE CITRATE FOR ENHANCED PCOS TREATMENT - BHATT, FORAM; PATEL, DIPTI (International Journal of Applied Pharmaceutics, 2026)
Objective: To develop and evaluate a novel dissolving microneedle patch containing clomiphene citrate‑loaded solid lipid nanoparticles (CC‑SLNs), aiming to enable sustained transdermal drug delivery for PCOS treatment, enhance therapeutic effectiveness, and reduce side effects linked to oral administration. Methods: CC‑SLNs were formulated using hot homogenization and ultra-sonication and optimized via a box–behnken design targeting ideal particle size, entrapment efficiency, drug loading, and zeta potential. Microneedle patches were fabricated from biocompatible polymers (polyvinyl alcohol, polyvinylpyrrolidone, polyethylene glycol 400), featuring 915 µm-high needles for effective dermal penetration. In vitro characterization assessed patch thickness, folding endurance ( 300 folds), moisture uptake, and drug release kinetics. Ex vivo release studies were performed on human skin models. For in vivo evaluation, female wistar rats were randomly assigned to control (saline), oral CC, or CC‑SLN microneedle patch groups (n = 6 each). Skin irritation (erythema and edema) was monitored at 1, 24, 48, and 72 h post-application, and at 72 h, blood samples were collected for LH, FSH, and insulin resistance evaluation. Skin biopsies were obtained for histopathological analysis. Results: SLN components were selected based on Particle size (242±11 nm), Zetapotential (25.6±0.9 mv) and PDI (0.24±0.02). Regression analysis was performed using design experts which displays the significance of p-value. Optimized batch was selected by point prediction and Batch No. 17 was selected. SEM study confirmed uniform and structurally. In vitro and ex vivo release studies demonstrated sustained drug release ( 89% over 5 days in vitro; 78% ex vivo). In vivo, the CCSLN patch delivered prolonged systemic activity, minimized hormonal fluctuations, and showed significantly reduced skin irritation and histopathological changes compared to oral administration. Conclusion: The developed CC‑SLN microneedle patch represents a promising transdermal approach for PCOS management. It delivers clomiphene citrate in a controlled and sustained manner, enhances treatment efficacy, and offers superior safety and tolerability relative to conventional oral therapy, based on pharmacodynamics, hormonal profiles, and dermal safety in a rat model.